Economic Entomology in the 21st Century, as Seen from a Bibliometric Analysis of Its Leading Journal, 2000–2015. Part II: Lepidoptera, Coleoptera, and Hemiptera. Issue 1 (2nd January 2018) - Stankus, Tony
ABSTRACT: In Part II of our study of papers published in the Journal of Economic Entomology, 2000–2015, we focus on the three most intensely studied orders: Lepidoptera, Coleoptera, and Hemiptera. Species within these orders account for 71 percent of the grand total of the studies of commodities attacked or venues infested. These species also account for 75 percent of the membership of the top one hundred species, and 69 percent of the top hundred's papers. Species within these orders include the world's most significant pests of apples, cabbages, cherries, corn, cotton, grapes, oranges, peaches, plums, potatoes, rice, soybeans, tomatoes, tree nuts, most warehoused dry commodities, wheat, and the most economically important hardwoods and conifers. Tables provided in this paper determine the relative rankings of species within these three orders among the top hundred.